Neural mechanisms of fairness decision-making: An EEG comparative study on opportunity equity and outcome equity - Qi Li; Ya Zheng; Jing Xiao; Kesong Hu; Zhong Yang (NeuroImage)
Social equity consists of opportunity equity and outcome equity, where outcome equity refers to the equitable distribution of resource, while opportunity equity refers to equivalent sets of opportunities to obtain a satisfactory outcome, ensuring equality in expected payoffs rather than the actual payoffs. Previous studies showed the existence of inequity aversion for opportunity inequality and identified some differences between opportunity equity and outcome equity in the behavior pattern of evaluation and reaction processes. However, the commonalities and distinctions in brain activity during the fairness decision-making of opportunity equity and outcome equity remain unclear. Our study used a modified version of the ultimatum game (UG) and the classic UG, and recorded electroencephalogram (EEG) data to investigate underlying neural mechanisms of fairness decision-making of opportunity equity and outcome equity. The EEG results revealed that both shared the same components of the P300 and delta bands associated with reward processing. Compared to outcome equity, opportunity equity did not identify conflict-related medial frontal negativity (MFN) and theta bands, but showed differences in the P2 and beta bands. Moreover, we used a computational modeling approach to estimate the utility for each trial, and found that larger P2 amplitudes were associated with lower utility in opportunity distribution, while larger P300 amplitudes were associated with higher utility in outcome distribution. Our findings provide electrophysiological evidence for the existence of opportunity equity and shed light on the cognitive processing disparities between opportunity equity and outcome equity. These results not only validate and expand the theory of inequality aversion but also empirically support the targeted resolution of social inequalities in various contexts.